2020
DOI: 10.1080/23802359.2020.1820396
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequence of Japanese forest green tree frog (Rhacophorus arboreus)

Abstract: We determined the complete mitochondrial genome sequence of the Japanese forest green tree frog (Rhacophorus arboreus). The mitochondrial genome is 22,236 bp in length, which encodes 13 proteincoding genes, 2 rRNA, and 22 tRNA genes, and two control regions (D-loops). The whole gene arrangement of R. arboreus was the same as that of Rhacophorus omeimontis and Rhacophorus schlegelii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…Eight tRNA genes ( tRNA Pro , tRNA Gln , tRNA Ala , tRNA Asn , tRNA Cys , tRNA Tyr , tRNA Ser(UCN) , and tRNA Glu ), and one PCG ( ND6 ) were encoded on the light strand (L-strand), while the remaining 14 tRNAs and 11 PCGs were encoded on the heavy strand (H-strand) ( Figure 1 ; Table S3 ). This H&L-strand gene distribution is congruent with all seven previously published rhacophorid mitogenomes [ 20 , 21 , 22 , 23 , 24 , 36 , 42 ]. Similar to the mitogenome of two other Polypedates frogs ( P. braueri and P. megacephalus ) [ 21 , 22 , 30 ], there was an NCR situated between gene tRNA Lys and ATP6 that is thought to be the original position of the absent ATP8 gene [ 22 , 30 ].…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Eight tRNA genes ( tRNA Pro , tRNA Gln , tRNA Ala , tRNA Asn , tRNA Cys , tRNA Tyr , tRNA Ser(UCN) , and tRNA Glu ), and one PCG ( ND6 ) were encoded on the light strand (L-strand), while the remaining 14 tRNAs and 11 PCGs were encoded on the heavy strand (H-strand) ( Figure 1 ; Table S3 ). This H&L-strand gene distribution is congruent with all seven previously published rhacophorid mitogenomes [ 20 , 21 , 22 , 23 , 24 , 36 , 42 ]. Similar to the mitogenome of two other Polypedates frogs ( P. braueri and P. megacephalus ) [ 21 , 22 , 30 ], there was an NCR situated between gene tRNA Lys and ATP6 that is thought to be the original position of the absent ATP8 gene [ 22 , 30 ].…”
Section: Resultssupporting
confidence: 89%
“…The length of the 16S rRNA gene was 1537 bp for P. impresus and P. mutus , and the size of 12S rRNA gene was 930 bp for P. impresus and 931 bp for P. mutus ( Table S3 ). As shown in Table 2 and Table S4 , both rRNA genes presented a high A+T preference of 59.0% for P. impresus and 59.9% for P. mutus , which was in line with the other seven rhacophorids [ 20 , 21 , 22 , 23 , 24 , 30 , 36 , 42 ]. Furthermore, the comparative analysis indicated that all nine Rhacophoridae species possessed a positive AT skew and a negative GC skew for both the 12S rRNA gene and 16S rRNA gene ( Table S4 ).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations